Meta-analysis of low-molecular-weight heparin to prevent recurrent placenta-mediated pregnancy complications - Rodger, Marc A.; Carrier, Marc; Le Gal, Grégoire; Martinelli, Ida; Perna, Annalisa; Rey, Évelyne; de Vries, J.I.P.; Gris, Jean-Christophe (Blood, 2014)
A 35-year-old woman with recurrent severe placenta-mediated pregnancy complications in her 2 pregnancies asks: Will low-molecular-weight heparin help prevent recurrent placenta-mediated pregnancy complications in my next pregnancy? We performed a meta-analysis of randomized controlled trials (RCTs) comparing low-molecular-weight heparin (LMWH) vs no LMWH for the prevention of recurrent placenta-mediated pregnancy complications. We identified six RCTs that included a total of 848 pregnant women with prior placenta-mediated pregnancy complications. The primary outcome was a composite of pre-eclampsia (PE), birth of a small-for-gestational-age (SGA) newborn (<10th percentile), placental abruption, or pregnancy loss >20 weeks. Overall, 67 (18.7%) of 358 of women being given prophylactic LMWH had recurrent severe placenta-mediated pregnancy complications compared with 127 (42.9%) of 296 women with no LMWH (relative risk reduction, 0.52; 95% CI, 0.32 to 0.86; P = .01; I2, 69%, indicating moderate heterogeneity). We identified similar relative risk reductions with LMWH for individual outcomes, including any PE, severe PE, SGA <10th percentile, SGA <5th percentile, preterm delivery <37 weeks, and preterm delivery <34 weeks with minimal heterogeneity. LMWH may be a promising therapy for recurrent, especially severe, placenta-mediated pregnancy complications, but further research is required.